Cyber-physical-social systems and constructs in electric power engineering - Suryanarayanan, Siddharth; Hansen, Timothy M.; Roche, Robin (IET power and energy series, 2016)
Cyber-physical-social systems (CPSS) integrate computing, physical assets, and human networks. Divided into four application areas to the electric grid, this book describes state-of-the-art CPSS in electric power systems, including detailed approaches on social constructs which are a critical aspect of the end-user realm. The book covers: Grid stability and security: distributed controls and algorithms for stability, cyber-security of generator units, and dynamic contingency analysis in the grid. Distribution system controls and economics: aggregators and agents for demand response, electric vehicles integration, smart neighborhoods, and microgrids. Social aspects and implementation: sociological customer interactions with the grid, SCADA systems, and occupants' roles in commercial buildings. Testbeds for validation: cyber-physical security assessment and distributed real time digital simulation. This book will be invaluable to academics and professional engineers engaged in cyber-physical social system applications for power engineering. It will also be of interest to social scientists, economists, and business personnel working on engineering applications for the Smart Grid, and students of power engineering.